KARAKTERISTIK MINYAK KAYU MANIS ( QNNAMOMUMBURMANII BLUME) BERDASARKAN I^TAKKULIT PADA BATANG DAN UKURAN BAHAN PADA PROSES PENYULINGAN - Noviar Harun (Jurnal Sagu, 2010)
The research objective was to determine the effect of skin hieation on the stem and material sizeduring distWation process toward yieM and quality of cinnamon oil {dimaimmutm bumuum Blume). Researchmethod used was fnctorial in Randomized Block Design with two treatments. The treatmoits were the location/height of skin (30cm, 60 cm and 90 cm from the base ofthe stem) and the size of the material (smaB, mediumand large). Replications were conducted three times and then continued with DNMRT test if there is anysignificant d ifference among the treatments. The parameters used were oil yieM, spedfic gravity, refractiveindex, optical rotation, solubility in akohol and total sinnamahiehide The result showed that the highest oilyield, specific gravity and refractive index contained in the combined treatment of higher locatiofl on stem (90cm) and smaller material size. Foroptiad rotation the highest value contained in combined treatment of tergermaterial size and higher skintocationon the stem (90 cm). The h h s value for the solubility in alcohol and% ettotal sinnamaklehHie contained in combined treatment oflarger size material and lower locatkin on the stem(30 cm). Cinnamon o8 produced still fulfils the quality standard of Indonesfain cinnamon oil (SN1).